Antimicrobial resistance of Neisseria gonorrhoeae in Latin American countries: A systematic review - Sandoval, María Macarena (2023)
Background: Detailed information is needed on the dynamic pattern of antimicrobial resistance (AMR) in Neisseria gonorrhoeae in Latin America and the Caribbean (LAC). Objectives: To conduct a systematic review of AMR in N. gonorrhoeae in LAC. Methods: Electronic searches without language restrictions were conducted in PubMed, Embase, Cochrane Library, EconLIT, Cumulative Index of Nursing and Allied Health Literature, Centre for Reviews and Dissemination, and Latin American and Caribbean Literature in Health Sciences. Studies were eligible if published between 1 January 2011 and 13 February 2021, conducted in any LAC country (regardless of age, sex and population) and measured frequency and/or patterns of AMR to any antimicrobial in N. gonorrhoeae. The WHO Global Gonococcal Antimicrobial Surveillance Programme (WHO-GASP) for LAC countries and Latin American AMR Surveillance Network databases were searched. AMR study quality was evaluated according to WHO recommendations. Results: AMR data for 38, 417 isolates collected in 1990–2018 were included from 31 publications, reporting data from Argentina, Brazil, Colombia, Peru, Uruguay, Venezuela and WHO-GASP. Resistance to extended-spectrum cephalosporins was infrequent (0.09%–8.5%). Resistance to azithromycin was up to 32% in the published studies and up to 61% in WHO-GASP. Resistance to penicillin, tetracycline and ciprofloxacin was high (17.6%–98%, 20.7%–90% and 5.9%–89%, respectively). Resistance to gentamicin was not reported, and resistance to spectinomycin was reported in one study. Conclusions: This review provides data on resistance to azithromycin, potentially important given its use as first-line empirical treatment, and indicates the need for improved surveillance of gonococcal AMR in LAC.